Market Study of Farstrack And Casio Watches (International Journal of Scientific Research and Management (IJSRM), 2014)
With the advent of new technology, a revolutionary change is occurred in the watch market of India. Previously only a few brands were ruling the market. However with the passage of time and with the opening of free trade, there is no dearth of various national and international brands in the market. A few years ago, people used to buy watch, only to check time. However, now they buy not only to check time but also for fashion. In the present report an attempt has been made to analyze the two brands of the watch namely, Fastrack and Casio by using technique of SWOT analyses and covering aspects such as marketing environment, advertising and position.